William Blake's animal symbols: tensions and intersections between science and allegory In Eighteenth-Century attitudes towards animals - Singh, Jyoti (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 2017)
This thesis explores the tensions and intersections between science, allegory, and related eighteenth-century attitudes towards animals in William Blake's poetry through detailed analysis of individual animal symbols and tropes. It will focus specifically on the period between 1794 and 1820, to coincide with the dates of Blake's major works. Chapter One outlines Blake's key philosophies, concentrating on his particular approach to symbolism. By rejecting certain Enlightenment ideals and beliefs surrounding allegory, Blake created his own form of the literary tradition, and the subjects and symbols of his poetry clearly demonstrate shifting allegorical frames. The chapter also explains why he argued for the recognition, and even valorisation, of the imaginative faculty, or "Poetic Genius" , in an era which accepted reason and rational thinking as one of the main means of apprehending the world. Chapter Two considers the significance of Blake's use of predatory animals in the SONGS Of INNOCENCE and Of EXPERIENCE. In focussing on symbolic animals, the chapter assesses whether the 'real' animals (with all their scientific associations) are alluded to, and the extent to which they influence their symbolic counterparts. In choosing these symbols to represent key themes throughout his oeuvre, Blake drew on some familiar associations and contemporary attitudes towards animals, but offered no critique of society's attitudes to animals. Chapter Three identifies and analyses the "fragments of Eternity" represented in the contraries of "Good" and "Evil" , and "Energy" and "Reason" embodied by the animals in THE MARRIAGE of HEAVEN and HELL. The symbols' division between "Reason" and "Energy" develops an understanding of the complex attitudes towards animals, both in Blake's mind, and in that of the eighteenth-century British public. Chapter Four is concerned with Blake's depictions of the Worm and Serpent in his poetry, and how his conception of "Beulah" provides more insight into these symbols and their functions. It also grapples with Rod Preece's argument that the poet recognised the sanctity and divinity in all forms of life, and sought to endorse these beliefs through his animal symbols. As the thesis illustrates, though, Blake is not arguing for the sanctity of all life to be upheld, nor does he see any divinity in the beings and objects found in nature. Sanctity and divinity are constructs of the imagination, and it is through exercising the imaginative faculty - the "Poetic Genius'' - along with our senses and instincts, that we are able to make sense of the world. The study thus concludes by considering the extent to which 'real' animals intrude upon Blake's oeuvre, and attempts to determine the value of reading the symbols through an "animal studies" paradigm. It also argues that 'real' animals are inseparable from their cultural and symbolic representations, because these are the only means of interpretation we have.
Keywords: Uncatalogued